A TbPc2 sub-monolayer deposit on a titanium dioxide ultrathin film: magnetic, morphological, and chemical insights. Issue 42 (4th October 2021) - Sorrentino, Andrea Luigi; Cimatti, Irene; Serrano, Giulia; Poggini, Lorenzo; Cortigiani, Brunetto; Malavolti, Luigi; Otero, Edwige; Sainctavit, Philippe; Mannini, Matteo; Sessoli, Roberta; Caneschi, Andrea
Abstract : Thin inorganic films ( i.e., metal oxides) are often used as decoupling layers to optimize the interactions between the molecular magnetic layers and metallic surfaces. Abstract : Thin inorganic films ( i.e., metal oxides) are often used as decoupling layers to optimize the interactions between the magnetic layers of molecules and metallic surfaces. For deposits of single-molecule magnets (SMMs), a decoupling layer can minimise the hybridization of the metallic substrate that is responsible for the quenching of their typical magnetic bistability. Here, we explored the potential of a single layer of titania to be used as a decoupling layer, which could represent an interesting playground for widespread use in many technological applications. We used a TiO2 monolayer with a lepidocrocite-like structure grown on a Ag(100) substrate for the deposition of the terbium(iii ) bis-phthalocyaninato (TbPc2 ) complex. A multi-technique approach employing X-ray photoelectron spectroscopy and scanning tunnelling microscopy was used to examine the integrity of a TbPc2 sub-monolayer deposit and to study the molecular adsorption configuration on the TiO2 film. Furthermore, X-ray magnetic circular dichroism was used to investigate the magnetic properties of the TbPc2 sub-monolayer, revealing that the TiO2 film successfully preserves the molecular spin character. X-ray-based magnetic measurements showed that the quantum tunnelling of the magnetization characterizing a bulk of molecules is still present and that the present titania film displays a decoupling effect of comparable efficiency to that of a graphene layer.